2015
DOI: 10.1111/his.12711
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade fetal adenocarcinoma of the lung is a tumour with a fetal phenotype that shows diverse differentiation, including high‐grade neuroendocrine carcinoma: a clinicopathological, immunohistochemical and mutational study of 20 cases

Abstract: Lung adenocarcinomas with H-FLAC features possess the potential for multidirectional differentiation, and are not strongly associated with known major driver gene mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
76
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 45 publications
9
76
0
1
Order By: Relevance
“…Our results demonstrated that H-FLAC tended to occur more frequently in elderly men with a history of heavy smoking but that L-FLAC was typically found in younger patients; these findings are consistent with the results of prior reports (2,4,7,10). Additionally, H-FLAC was often at an advanced stage at presentation, with a poor prognosis; in contrast, L-FLAC, was predominantly at stage I, with favorable outcomes (2,4).…”
Section: Molecular Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results demonstrated that H-FLAC tended to occur more frequently in elderly men with a history of heavy smoking but that L-FLAC was typically found in younger patients; these findings are consistent with the results of prior reports (2,4,7,10). Additionally, H-FLAC was often at an advanced stage at presentation, with a poor prognosis; in contrast, L-FLAC, was predominantly at stage I, with favorable outcomes (2,4).…”
Section: Molecular Characteristicssupporting
confidence: 93%
“…Histologically, both prior reports and our findings indicated that H-FLAC histology is commonly combined with other histologies (4,10). Morita et al reported that H-FLACs were invariably admixed with components of other lung cancer types.…”
Section: Molecular Characteristicssupporting
confidence: 74%
See 2 more Smart Citations
“…The relationship between prognosis and rare variants has been less examined (4,5), and past studies (6)(7)(8)(9) have focused primarily on the relationship between prognosis and major histological patterns. These studies examined the relationship between prognosis and classification, and indicated that patients with lepidic predominant adenocarcinomas had the most favorable outcome of all subtypes of invasive lung adenocarcinoma.…”
mentioning
confidence: 99%